Trends in uptake of the 75+ health assessment in Australia: a decade of evaluation - Hamirudin, Aliza Haslinda; Ghosh, Abhijeet; Charlton, Karen; Bonney, Andrew; Walton, Karen (CSIRO, 2015)
In Australia, older adults aged 75+ years are encouraged to avail themselves of the comprehensive 75+ health assessment (75+ HA) to identify medical conditions and highlight potential risk factors for poor health. However, uptake of this item has been reported to be low. This study aimed to identify the uptake of the 75+ HA within regional areas of New South Wales and compare this against state and national trends over an 11-year period. Data on uptake of the 75+ HA for item numbers 700 and 702, from 1999 until 2010, were obtained from the Medicare Australia portal and Department of Health and Ageing databases. Trends over time were collated and compared at the regional, state and national level. The study found that an increasing number of the 75+ HAs were performed from 1999 to 2009. Overall, the uptake of the 75+ HA is generally low across Australia, at ~20% of the eligible population, but varied across states and even regions within states. The study also revealed that despite low uptake encouraging trends were evident over a decade of 75+ HA implementation. It is argued that strategies in improving the uptake should be targeted for early identification of health risk and overall improved quality of health in older adults.